The Analysis of Social Media Addiction Level on Adolescents - Netrawati Netrawati; Rizki Wulandari; Yeni Karneli; Yarmis Syukur (International Journal of Research in Counseling and Education, 2020)
The ease of long-distance interaction makes social media a necessity that must exist in every individual's life, which causes a person to have an uncomfortable feeling if they cannot access social media. Indirectly, accessing social media can result in some people who have social media addiction. Others desire to be noticed by others, difficulty communicating directly in their social environment, which makes them prefer to spend time interacting through social media. The phenomenon that happens is excessive and repeated use of social media every day, loss of self-control, which causes the long duration of use, unconsciousness of negative consequences to themselves and those around them, tolerance of social media. Emerges the withdrawal symptoms when trying not to access social media, such as feelings of discomfort in addicted adolescents. This study aimed to find out the description of the level of social media addiction among adolescents in Padang. The method used in this study was descriptive research with quantitative methods. The sample used in this study was 250 adolescents. From the data collection results, it was generally found that adolescents are in the low category with an achievement of a percentage, 51.2%. Then, adolescents are in the medium category with a percentage, 42.4%, and some adolescents are in the high category with an achievement, 1.6%.